2006
DOI: 10.1007/s10856-006-8232-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the porosity of hydroxyapatite ceramics on in vitro and in vivo bone formation by cultured rat bone marrow stromal cells

Abstract: The in vitro and in vivo osteoblastic differentiation of rat bone marrow stromal cells (MSCs) was assessed on hydroxyapatite disks with 3 different porosities: 30%, 50%, and 70% (HA30, HA50, and HA70, respectively). MSCs obtained by 10-day culture of fresh bone marrow cells were subcultured for 2 weeks on 3 kinds of porous HA disks in the presence and absence of dexamethasone (Dex). After 2 weeks of subculture, alkaline phosphatase (ALP) activity and osteocalcin production of MSCs/HA composites with Dex were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 19 publications
2
65
0
2
Order By: Relevance
“…It has been reported that several weeks are required to prepare and differentiate MSCs to osteoblastic cells for transplantation (i.e., primary culture in standard medium for 10 d followed by a subculture in differentiation medium for 2 weeks Okamoto et al, 2006)). In contrast, the present procedure shortened the time required for transplantation to approximately 10 d. These results show the usefulness of our in vitro cell culture expansion-differentiation technique using an osteogenic (FGF+) condition, which was confi rmed after in vivo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several weeks are required to prepare and differentiate MSCs to osteoblastic cells for transplantation (i.e., primary culture in standard medium for 10 d followed by a subculture in differentiation medium for 2 weeks Okamoto et al, 2006)). In contrast, the present procedure shortened the time required for transplantation to approximately 10 d. These results show the usefulness of our in vitro cell culture expansion-differentiation technique using an osteogenic (FGF+) condition, which was confi rmed after in vivo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, it is not clear that the combination of BMPs and DAG will enhance or accelerate the in vitro differentiation of osteoblasts and if these factors are stage limiting. Several authors also reported that biomaterials such as tricalciumphosphate (TCP), hydroxyapatite (HA), 22 and collagen I [23][24][25] have osteoblast-promoting potency. Beside the physico-chemical properties of these biomaterials, surface parameters such as porosity, microarchitecture, and topography significantly influence cellular adherence, migration, proliferation, differentiation, and survival of osteoprogenitor cells.…”
mentioning
confidence: 99%
“…Beside the physico-chemical properties of these biomaterials, surface parameters such as porosity, microarchitecture, and topography significantly influence cellular adherence, migration, proliferation, differentiation, and survival of osteoprogenitor cells. 22 In this study, the in vitro osteogenic potential of BMP-2, DAG, and collagen I/III are investigated by utilizing a human bone marrow cell culture.…”
mentioning
confidence: 99%
“…The ≈ 66 % interconnected macroporosity, previously reported as an optimal value (Okamoto et al, 2006), associated with a dense shell limiting medium flow bypass between the chamber wall and the scaffold sides, was homogeneously seeded and perfused. More generally, the high control of macropore and interconnection diameters, micropore density, phase and chemical composition of the scaffolds, as well as the setting up of appropriate seeding and perfusion protocols allowed uniform cell colonisation …”
Section: Discussionmentioning
confidence: 83%